Examples of principles behind the industrial metallic products - Mac, Yoshiharu (Frontiers in Engineering Innovation Research, 2003)
Not recognized in general but in fact, theories and what we could call principles are often hidden behind the industrial products. Here three examples of such kind are introduced. The first one shows the relationship between mechanical properties, crystallographic orientation and manufacturing conditions. The second one shows the way of applying the chracteristics of intermetallic compound to the real product. The third one shows the way of applying the electrochemistry to the real product